Hanukkah in America : a history - Ashton, Dianne (Goldstein-Goren series in American Jewish history., 2013)
In New Orleans, Hanukkah means decorating your door with a menorah made of hominy grits. Latkes in Texas are seasoned with cilantro and cayenne pepper. Children in Cincinnati sing Hanukkah songs and eat oranges and ice cream. While each tradition springs from its own unique set of cultural references, what ties them together is that they all celebrate a holiday that is different in America than it is any place else. For the past two hundred years, American Jews have been transforming the ancient holiday of Hanukkah from a simple occasion into something grand. The ways in which Hanukkah was reshaped by American Jews reveals the changing goals and values that emerged among different contingents each December as they confronted the reality of living as a religious minority in the United States. Bringing together clergy and laity, artists and businessmen, teachers, parents, and children, Hanukkah has been a dynamic force for both stability and change in American Jewish life. Drawing on a varied archive of songs, plays, liturgy, sermons, and a range of illustrative material, as well as developing portraits of various communities, congregations, and rabbis, this book reveals how an almost forgotten festival became the most visible of American Jewish holidays.